Toward a combined merchant-regulatory mechanism for electricity transmission expansion - William Hogan; Juan Rosellón; Ingo Vogelsang (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Electricity transmission pricing and transmission grid expansion have received increasing regulatory and analytical attention in recent years. Since electricity transmission is a very special service with unusual characteristics, such as loop flows, the approaches have been largely tailor-made and not simply taken from the general economic literature or from the more specific but still general incentive regulation literature. An exception has been Vogelsang (2001), who postulated transmission cost and demand functions with fairly general properties and then adapted known regulatory adjustment processes to the electricity transmission problem. A concern with this approach has been that the properties of transmission cost and demand functions are little known but are suspected to differ from conventional functional forms. The assumed cost and demand properties in Vogelsang (2001) may actually not hold for transmission companies (Transcos). Loop-flows imply that certain investments in transmission upgrades cause negative network effects on other transmission links, so that capacity is multidimensional. Total network capacity might even decrease due to the addition of new capacity in certain transmission links. The transmission capacity cost function can be discontinuous. There are two disparate approaches to transmission investment: one employs the theory based on long-run financial rights (LTFTR) to transmission (merchant approach), while the other is based on the incentive-regulation hypothesis (regulatory approach). An independent system operator (ISO) could handle the actual dispatch and operational pricing. The transmission firm is regulated through benchmark or price regulation to provide long-term investment incentives while avoiding congestion. In this paper we consider the elements that could combine the merchant and regulatory approaches in a setting with price-taking electricity generators and loads.
Keywords: D24; L51; L94; 330; Electricity transmission; Incentive regulation; Financial transmission rights; Loop-flow problem